ORANG MUNA YANG TIDAK BISA BERBAHASA MUNA - Hasmini Hasmini (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This study aims to find out and to describe the language used in everyday life by the Muna's people and the reason for the inability of the Muna people to speak in Muna language. This research is qualitative descriptive research. Data collection is done through observation techniques involved and in-depth interviews. The results of this study indicate that the language commonly used in everyday life by Muna people in Laiworu Village is Indonesian as the main language of both communications within the family, school, market, and in the environment in which they work. Some of the things that underlie Muna people in Laiworu Village cannot speak Muna language, among others: (1) because of the emergence of feelings of inferiority or prestige when using regional languages in daily communication, especially among teenagers. They do not want to be labeled as villagers; (2) They live in settlements that tend to be multicultural, and (3) mixed marriages. Nevertheless, Muna Language can still be found in the interaction of the local community. But in a limited situation, that is only when meeting parents who are elderly or are meeting with people from the village. Keywords: Muna’s people, Muna language, Laiworu Village